The Effect of Independent Commissioners, Audit Committee Activities, and Firm Complexity on Audit Fee in Banks - Muhammad Nur Maftuh Ihsan; Rizdina Azmiyanti (Jurnal Akuntansi, 2026)
This study investigates the effect of independent commissioners, audit committee activity, and firm complexity on audit fees in banking firms listed on the Indonesia Stock Exchange during 2022-2024. A quantitative approach is employed using secondary data from annual reports and audited financial statements, resulting in 120 firm-year observations selected through purposive sampling. The data are analyzed using multiple linear regression with SPSS. The findings reveal that independent commissioners, audit committee activity, and firm complexity each have a positive and significant effect on audit fees. A higher proportion of independent commissioners strengthens supervisory effectiveness, leading to broader audit scope. Increased audit committee activity enhances monitoring of financial reporting and audit processes, resulting in additional audit procedures. Meanwhile, greater firm complexity increases audit difficulty due to more extensive operations and transactions, requiring higher auditor effort. Overall, corporate governance mechanisms and firm complexity significantly influence audit fee determination in the banking sector.